'Dear Fabulous!' Personal and Professional Identities evolving in the interactional context of self-reflection. (30th May 2016) - Jagoe, Caroline; Walsh, Irene
Abstract : Reflective practice, particularly that linked to clinical learning in the context of service learning pedagogies, has the potential to influence the development of students' identities, particularly for students on professional courses (e.g. in healthcare contexts). Data drawn from first year speech and language therapy students' selfdirected letters ('Dear me…') are analysed through the lens of a thematic content analysis, using the tool of Leximancer. This data represents twenty-one students' written reflections on anticipated ('before') and completed ('after') interactions with a person with a communication disorder. In addition to an analysis of 'before' and 'after' reflections (via the 'Dear me…' letters), the analysis considers the data as an internal dialogue that takes place over time with the students' reflective selves. The data will demonstrate a broadening view of a more 'considered self' and increasing acknowledgement and consideration of the 'other' (i.e. another person). The development of a future professional identity emerges as just one facet of identity work within the context of reflections on personal development and growth, in the safe environment of letters to self.